PENGARUH STRATEGI PEMBELAJARAN RELATING, EXPERIENCING, APPLIYING, COOPERATING, TRANSFERRING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS X MIPA SMAN 5 BUKITTINGGI - Fitri Ramadhani (Departemen Matematika, 2019)
One of the goals of mathematics learning is to understand the concepts of mathematics. But in reality, students' understanding of mathematics concept in SMAN 5 Bukittinggi wasn’t optimal, it seen from the results of the test given. The solution was applied strategy of REACT. The purpose of the research was both to describe understanding of mathematics concepts of students who studied with the strategy of REACT and to describe whether understanding of mathematics concepts of students who studied with the strategy of REACT was better than understanding of mathematics concepts of students who studied with direct learning models. The type of research was quasy experiment and descriptive research with the static group design research design. Based on the results of the quiz, tests and hypothesis testing, an increase in understanding the concepts of students is obtained and understanding the concepts of students who learn to use REACT strategy is better than understanding the concepts of students who learn with direct learning models. It can be concluded that the REACT strategy influences understanding of mathematics concepts. Keywords – REACT Learning Strategies, Understanding of mathematical concepts.